Online Shopping Hestitation Model: A Survey In Bandung Jawa Barat - Sugianto, Paulus; Ary Novianto, Robertus (International Journal of Psychosocial Rehabilitation, 2020)
The development of internet technology allows the second stage of the internet bubble, in which the use of the internet as a tool to conduct transactions and the exchange of goods or the sale of goods is increasingly widespread. In Indonesia, there are not too many companies selling online, but it is already rife because many individuals or companies sell products by marketing them on increasingly social networks in Indonesia, such as Facebook. Although still rampant, there are still many who have not done the process of shopping online on the internet. The basic model of this study was taken from Cho et al. (2006) in his research titled Online Shopping Hestitation. According to Cho et al., doubts about shopping online are caused by four supporting factors such as uncertainty, media/channel innovation, contextual factors, and customer characteristics. Each factor has sub-factors that support the main factors; based on this basic model, a research model is then developed by adding several sub-factors from Turban and Mathew (2001). This study aims to determine what factors influence a person to refuse to shop on the internet. The study was conducted by conducting a survey in Bandung, West Java, and from 90 samples distributed, 75 individual respondents were collected to see factors that influence individuals to delay or even refuse to shop online. Model testing uses partial least squares (pls) data processing methods for hypothesis testing. The results of this study are the basic model and additional sub-factors proved that of the 17 sub-factors studied, 15 sub-factors affect the doubt in shopping online and only 2 sub-factors have not been proven to influence doubts in shopping online.